2019
DOI: 10.1073/pnas.1909992116
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-level engineering and imaging of polypeptoid crystal lattices

Abstract: Rational design of supramolecular nanomaterials fundamentally depends upon an atomic-level understanding of their structure and how it responds to chemical modifications. Here we studied a series of crystalline diblock copolypeptoids by a combination of sequence-controlled synthesis, cryogenic transmission electron microscopy, and molecular dynamics simulation. This family of amphiphilic polypeptoids formed free-floating 2-dimensional monolayer nanosheets, in which individual polymer chains and their relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
135
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(145 citation statements)
references
References 33 publications
10
135
0
Order By: Relevance
“…The detailed protocol for polypeptoid synthesis can be found in Xuan et al (2019). Two sequence-defined di-block copolypeptoid decamers, with four hydrophilic monomers and six hydrophobic monomers, were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed protocol for polypeptoid synthesis can be found in Xuan et al (2019). Two sequence-defined di-block copolypeptoid decamers, with four hydrophilic monomers and six hydrophobic monomers, were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…They are similar to polypeptides except for the fact that the side chain is appended to the nitrogen atom rather than the α-carbon (Nam et al, 2010; Robertson et al, 2014). Crystalline polypeptoid membranes, which are only one unit-cell thick, similar to 2D protein membranes but with smaller unit cells, are generated by the self-assembly of di-block copolymers in dilute solutions (Jiang et al, 2018, 2019; Xuan et al, 2019). In a previous study, we have used images of untilted specimens to determine the structure of crystalline polypeptoid membranes with about 2 Å resolution when using vitrified specimens prepared on a holey carbon support film (Jiang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that substituents could be introduced onto the aromatic groups and varied without disrupting the packing preferences within the lattice. [76] We synthesized a series of diblock copolypeptoid decamers composed with the same hydrophilic poly(N-2(2-(2methoxyethoxy)ethoxy)ethylglycine) (pNte) block and different N-2-phenylethylglycine-based hydrophobic blocks bearing a systematic series of aromatic ring substituents, varying in size and their electron withdrawing or donating character (Figure 3A). These sequence variants all formed free-floating 2D monolayer nanosheets.…”
Section: Engineering the Atomic Structure Of Nanosheet Interiormentioning
confidence: 99%
“…Peptoid backbones preferentially generally adopt all cis-amide conformation in peptoid crystals regardless of the chemistry of side chains, as previously reported. [52,62,76] However, free in solution, peptoids undergo cis-trans isomerization due to the similar energy of the two conformers. A common strategy to induce one conformer over the other is to utilize local non-covalent interactions, including n→π*, steric, electronic, and hydrogen bonding interactions, to regulate the amide bond rotation of peptoid backbones.…”
Section: Engineering the Atomic Structure Of Peptoid Chain Conformationmentioning
confidence: 99%
“…Peptoids, comprising N-substituted glycines, are an emerging class of peptidomimetic molecules that offer biocompatibility, low-cost synthesis, high chemical flexibility, and designable sequences and performances (42)(43)(44). In a recent study, Xuan et al (45) demonstrated that peptoid architectures could be engineered at the atomic level, resulting in a variety of atomically defined structural arrangements. Compared to peptides, peptoids possess high conformational flexibility and confer a high degree of resistance to proteolytic degradation (44,46), due to the side chains located on the nitrogen of the amide backbone instead of the α-carbon.…”
mentioning
confidence: 99%